KONTRIBUSI BUDAYA ORGANISASI DAN IKLIM ORGANISASI TERHADAP KOMITMEN ORGANISASI - DANISWARA, ARFIAN (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: PT Bank Tabungan Negara move in the banking world. Each company must have an organizational culture and organizational climate as well as PT Bank Tabungan Negara cabang Surabaya, such as the creation of a good relationship between employees with one another as well as with superiors, whether in relationship, communication and cooperation. The data used are the primary and secondary data obtained via the question form, documents and interviews. Sample using the method of sampling universe that includes all employees in the loan service and transaction processing PT Bank Tabungan Negara with total 56 employees. Methods of data analysis using Multiple Linear Regression that assisted with SPSS software. The results indicates that the variable organizational culture and Organizational climate is the simultaneous effect of significant organizational commitment variable. Organizational culture partially significant influence on organizational commitment and Organizational climate partially significant influence on organizational commitment. Keywords: organizational culture, organizational climate,and organizational commitment.